An Empirical Study on Employee Exit Management Practices in Software Industries - Kiran Kumar Thoti, Dr.; Roselina Ahmad Saufi, Prof. Dr. (International Journal of Engineering and Technology, 2018)
Employee exit management describes the consciously designed separation process when an employee leaves the company, for which he has previously worked within the scope of a work or service contract. It deals with the formal processes revolving around an employee’s exit from an organization either through voluntary resignation, layoffs or termination. The exit management study was conducted in Virtusa Polaris Pvt Ltd, Chennai in Tamil Nadu. The total number sample was 100. The data was collected from the software employees who are leaving organization and in notice period.